Pengaruh Kombinasi Pemberian Jus Jambu Biji Merah dan Madu Terhadap Kadar Hemoglobin Ibu hamil - Suryani, Suryani; Kusmaryati, Pauline; Irbawati, Marlita; Suryanti, Yuli (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
The prevalence of pregnant women at risk of developing anemia with iron deficiency is around 35-75%, and increases with increasing gestational age. One fruit that can increase hemoglobin levels is guava. The combination of guava contains amino acids (tryptophan, lysine), calcium, phosphorus, iron, sulfur, vitamin A, vitamin B1 and vitamin C. This study aims to determine the effect of the combination of giving red guava juice and honey on maternal hemoglobin levels. pregnant at the Payo Selincah Community Health Center, Jambi City. This research is a quantitative research using the research design "Pre Experimental Pre-Post Test With One Group". This research was carried out at the Payo Selincah Community Health Center in January-July 2024. The population in this study was pregnant women in the third trimester from December 2023 to January 2024, totaling 30 people. The sample in this study was 30 people using the sampling technique in this study, total sampling. The data analysis method used is univariate and bivariate using the Paired T-Test statistical test. The results of the study showed that the average hemoglobin level before the combination of giving red guava juice and honey was 10.40, the average hemoglobin level after the combination of giving red guava juice and honey was 11.66, and there was an effect of the combination of giving guava juice. red seeds and honey on hemoglobin levels of pregnant women with a p-value of 0.000. It can be concluded that there is an influence of the combination of giving red guava juice and honey on the hemoglobin levels of pregnant women at the Payo Selincah Community Health Center. It is hoped that this research will be used as a reference and guide for community health centers to prevent and overcome the problem of low Hb levels in pregnant women by using red guava juice and honey.